2019
DOI: 10.3390/nu11030570
|View full text |Cite
|
Sign up to set email alerts
|

Is A Healthy Diet Associated with Lower Anthropometric and Glycemic Alterations in Predisposed Children Born from Mothers with Gestational Diabetes Mellitus?

Abstract: Children born from mothers with gestational diabetes mellitus (GDM) are at high-risk of obesity and type 2 diabetes. To date, there is a lack of effective strategies to prevent these complications. The aim of this study was to evaluate the association between diet quality and anthropometric and glycemic profiles of children exposed (GDM+) and unexposed (GDM–) to GDM. A total of 104 GDM+ and 38 GDM– children were included. Two 24-h dietary recall questionnaires were used to assess dietary intakes. The Healthy E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We observed a consistent protective effect of consuming a diet more aligned with the Dietary Guidelines for Americans across five different measures of adiposity for offspring exposed to GDM. This aligns with a recent Canadian study that reported a 75% reduced prevalence of overweight/obesity among offspring exposed to GDM who consumed a diet more aligned with the Canadian Food Guide . These results suggest that fetal overnutrition does not definitively program offspring to exhibit increased adiposity, but rather increases vulnerability for developing greater adiposity in the presence of an obesogenic environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a consistent protective effect of consuming a diet more aligned with the Dietary Guidelines for Americans across five different measures of adiposity for offspring exposed to GDM. This aligns with a recent Canadian study that reported a 75% reduced prevalence of overweight/obesity among offspring exposed to GDM who consumed a diet more aligned with the Canadian Food Guide . These results suggest that fetal overnutrition does not definitively program offspring to exhibit increased adiposity, but rather increases vulnerability for developing greater adiposity in the presence of an obesogenic environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no difference in obesity risk according to physical activity, and diet was not assessed. Another study of Canadian children reported that those who were exposed to GDM and consumed a healthy diet were four times more likely to be overweight/obese than children who were exposed but did not consume a healthy diet . Given the increasing number of individuals who are exposed to maternal diabetes in utero each year, a better understanding how early life health behaviours may mitigate the adverse effects of this exposure is needed to guide the development of targeted prevention efforts for children at highest risk of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…It is in this setting that managing nutrition comes to the fore as one of our few levers for preventing and managing GDM, the progression to type 2 diabetes, and, with these, potentially the life-long risk of cardiometabolic disease in the offspring. This special issue "Nutrition and Gestational Diabetes" comprises 14 peer-reviewed papers [6][7][8][9][10][11][12][13][14][15][16][17][18][19] that provide insight into different nutritional aspects relating to GDM. These papers address diet, gestational weight gain, and dietary patterns associated with the risk of GDM in the mother and/or offspring (n = 8), and with "better" GDM outcomes, including the long-term risk to the offspring (n = 2).…”
mentioning
confidence: 99%
“…The penultimate paper in the special issue also touched on the use of alternative screening tests [18] and showed poor utility of the fructosamine test to predict second trimester and postpartum glycaemia. The final paper [19] looked at 142 children with a mean age of 6-7 years and found that a healthy diet is associated with a better cardiometabolic health profile in children of women with previous GDM, including a lower risk of being overweight or obese.…”
mentioning
confidence: 99%